If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 2(y + -6) = 4(y + 2) + -2 Reorder the terms: 7y + 2(-6 + y) = 4(y + 2) + -2 7y + (-6 * 2 + y * 2) = 4(y + 2) + -2 7y + (-12 + 2y) = 4(y + 2) + -2 Reorder the terms: -12 + 7y + 2y = 4(y + 2) + -2 Combine like terms: 7y + 2y = 9y -12 + 9y = 4(y + 2) + -2 Reorder the terms: -12 + 9y = 4(2 + y) + -2 -12 + 9y = (2 * 4 + y * 4) + -2 -12 + 9y = (8 + 4y) + -2 Reorder the terms: -12 + 9y = 8 + -2 + 4y Combine like terms: 8 + -2 = 6 -12 + 9y = 6 + 4y Solving -12 + 9y = 6 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -12 + 9y + -4y = 6 + 4y + -4y Combine like terms: 9y + -4y = 5y -12 + 5y = 6 + 4y + -4y Combine like terms: 4y + -4y = 0 -12 + 5y = 6 + 0 -12 + 5y = 6 Add '12' to each side of the equation. -12 + 12 + 5y = 6 + 12 Combine like terms: -12 + 12 = 0 0 + 5y = 6 + 12 5y = 6 + 12 Combine like terms: 6 + 12 = 18 5y = 18 Divide each side by '5'. y = 3.6 Simplifying y = 3.6
| 5k=-20 | | x+30=103 | | w/6=-6 | | x+(x/100)x=56 | | -2y-19=6y+13 | | -1=n+1 | | 8=d+10 | | d+6=15 | | 3=k-3 | | (3z^(18/5))-(11z^(8/5))-(4z^(-2/5)) | | a-2=-9 | | 9-12+6= | | 2v+10=28 | | x/-5=-3 | | -5=x+5 | | a/7=-4 | | -7n=-21 | | b/-4=-5 | | 16+12-20= | | 2y+6=6y-18 | | 6x+8=-3x+-10 | | -3(-x-4)-17=-9(x+0) | | d+7=-4 | | w-9=-16 | | a-9=-6 | | 2*1*1+6*1-5= | | n+3=9 | | -10+b=-1 | | (x-1)/3-(x-1)/2=6 | | w/3=7 | | n+9=16 | | 3+n=1 |